Effects of light stimulion Desmodium Gyrans lateral leaflet movement Rhythms - Miah, M. Idrish; Johnsson, Anders (BRAC University, 2010)
Rhythmic up - down movements of the lateral leaflets in the plant Desmodium gyrans (L.F.) DC. have been studied. Leaflet movements were recorded with a video-computer system, where the digital video signals from the CCD camera were processed in an ATARI 1040 ST computer using special software. The average period of the lateral leaflet movements at 240C was estimated to be 3.5 min. It is proposed, however, that the rhythmic movements of the lateral leaflets might be due to the movement of water across the motor cells, i.e. shrinking and expansion of motor cells, andproton pumps, membrane potential changes and ion transports are responsible for water uptake and loss in motor cells. Leaflet movements in the presence of light stimuli were then studied. It was found that the leaflet always moved towards the direction of the light, whether it was applied from the abaxial or from the adaxial part of the pulvinus. A strong effect was found in both instances, namely the reduced amplitude of the leaflet movement and thus a shortened period. When the abaxial part was exposed to light, the leaflet oscillated in a lower position, but when the adaxial part was illuminated, it oscillated in an upper Detailed instructions for typing your article are given in the following. Since you have to send a camera-ready paper, you are personally responsible of the quality and appearance of your work. Please remember the following points in Particular: a) type upto 200 word abstract single column, b) use 9 pt Times New Roman font and single spaced lines for abstract, c) type the body of the paper in double columns, d) use 10 pt Times New Roman font and single spaced lines for body text, e) list of references in numerical order of appearance, f)supply good quality of figures and tables, g) the use of SI units is mandatory, h) no separate nomenclature, i) paper length should be limited to 10 pages, j) prepare the manuscripts in MSWORD selecting US letter size paper (8.5″×11″), k) manuscripts should be submitted in DOS formatted 3.5′′ FDD along with a hard copy or E-mail the manuscripts and post the hard copy.